1986
DOI: 10.1128/aac.30.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Delayed treatment with combinations of antiviral drugs in mice infected with herpes simplex virus and application of the median effect method of analysis

Abstract: Mice were inoculated intracerebrally with a lethal dose of herpes simplex virus type 2. Three days later, the mice were treated intraperitoneally, twice daily for 4 days, with the following drugs alone or in combination: acyclovir (ACV), vidarabine (ara-A), 2'-fluoro-5-iodoaracytosine (FIAC), and 2'-fluoro-5-methylarauracil (FMAU). Despite delayed treatment, most of the animals receiving low doses of FMAU alone or in combination with ACV or ara-A survived. In contrast, significantly higher mortality rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…To study whether AZT would interfere with the anti-HCMV effect of PFA, the effects of four appropriate combinations (1:1, 1:2, 1:5, and 1:10) of the two compounds on the multiplication of HCMV Ad169 in HEL fibroblasts were studied. Whereas AZT was found to be virtually without inhibitory effect even at concentrations up to 200 ,uM (data not shown), a dose-dependent inhibition was obtained for PFA with an EC50 of 34 ,uM (Table 3). Although AZT did not significantly inhibit HCMV multiplication, an EC50 of 383 ,uM was extrapolated (data not shown) in order to calculate the CI values for the studied combinations.…”
Section: Effects In Hiv-mentioning
confidence: 99%
See 1 more Smart Citation
“…To study whether AZT would interfere with the anti-HCMV effect of PFA, the effects of four appropriate combinations (1:1, 1:2, 1:5, and 1:10) of the two compounds on the multiplication of HCMV Ad169 in HEL fibroblasts were studied. Whereas AZT was found to be virtually without inhibitory effect even at concentrations up to 200 ,uM (data not shown), a dose-dependent inhibition was obtained for PFA with an EC50 of 34 ,uM (Table 3). Although AZT did not significantly inhibit HCMV multiplication, an EC50 of 383 ,uM was extrapolated (data not shown) in order to calculate the CI values for the studied combinations.…”
Section: Effects In Hiv-mentioning
confidence: 99%
“…A computer program obtained from ElsevierBiosoft, Cambridge, United Kingdom, was used for automatic analysis of all dose-effect data. Additional details on using this method have been reported previously (34). and correlation coefficients obtained from the median-effect plots of AZT, PFA, and their combinations, respectively.…”
mentioning
confidence: 99%
“…Selection of resistant virus in MT-2 cells was performed as previously described (20 Data analysis. The EC50 and median inhibitory concentrations were determined by the median effect method as described previously (7,32). Table 1 shows that week 7 viruses had become more than 1,000-fold resistant to both (-)-BCH-189 and (-)-FTC.…”
Section: Methodsmentioning
confidence: 99%
“…These antiviral agents are not cytotoxic in vitro and have a favorable pharmacological profile in animal models and in humans (32,41). Additional preclinical studies have demonstrated that the 5'-triphosphates of (-)-FTC and (-)-BCH-189 are competitive inhibitors of HIV-1 reverse transcriptase (RT) and are potent DNA chain terminators when HIV-1 RT is used (13,35).…”
mentioning
confidence: 99%
“…The median effective concentration (EC50) was determined by using at least four different concentrations of each compound. These values were derived from the computer-generated median effect plot of the dose-effect data as described previously (1,2,18). The EC50s obtained with the different compounds with recombinant and virion-associated RT are compared in Table 1.…”
mentioning
confidence: 99%